A study on enforcement of Joint Management Body (JMB) establishment in Selangor / Muhamad Azri Aini - Aini, Muhamad Azri (Faculty of Architecture, Planning and Surveying, 2009)
The implementation of Building and Common Property (Maintenance and Management) 2007 Act, 663 Act which is came into force in the aspect of property maintenance and management on 12 April 2007 is one of the latest government’s mechanism in order to increase government’s delivering systems which is to improve development and property maintenance and management matters especially to overcome all the problem that existed all this while in the strata properties. Nevertheless, the execution that just came into force for only 2 years already creates their own problems and need special attention in order to overcome these problems early as possible. Main objective for this Academic Project (PA) research is to look into execution of the 663 Act in general and specially will be focus on the problems that create and exist in the execution and setting up of the Joint Management Body (JMB) due to these entities are just being introduced in the strata properties and also to give the reasonable suggestions that could be taken in order to overcome all these problems. Information are gathered from previous researches, various academic papers, related issued articles, newspapers, journals, internet, professionals and peoples’ opinions who are either directly or indirectly involved in the execution of the 663 Act apart interviews and structured research involving questionnaire form that has been conducted to many of the respondents. The author hope this PA research will be a guidance and reference to the respective parties in order to know how these problems give their effects to the effective and efficient execution of the 663 Act and further could be a reference to these respective parties in order to look the best solutions to overcome these created and existed problems.